2022
DOI: 10.3390/biology11010143
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Control of Zika Infection Is Independent of Interferon Type I and Type III Expression

Abstract: Zika virus (ZIKV) is a pathogenic neurotropic virus that infects the central nervous system (CNS) and results in various neurological complications. Astrocytes are the dominant CNS cell producer of the antiviral cytokine IFN-β, however little is known about the factors involved in their ability to mediate viral infection control. Recent studies have displayed differential responses in astrocytes to ZIKV infection, and this study sought to elucidate astrocyte cell-specific responses to ZIKV using a variety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…ZIKV is a pathogenic neurotropic virus that crosses the blood‐brain barrier, infects the CNS of adults, and causes various neurological complications 34 . ZIKV has been detected in the brains and CSF of adults 10,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZIKV is a pathogenic neurotropic virus that crosses the blood‐brain barrier, infects the CNS of adults, and causes various neurological complications 34 . ZIKV has been detected in the brains and CSF of adults 10,35 .…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV is a pathogenic neurotropic virus that crosses the bloodbrain barrier, infects the CNS of adults, and causes various neurological complications. 34 ZIKV has been detected in the brains and CSF of adults. 10,35 In adult mice, ZIKV preferentially targets memory-related brain regions, inhibits hippocampal long-term potentiation, and induces memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Among the ZIKV dysregulated cellular functions at 48 h post ZIKV infection, which was the timepoint with the largest number of dysregulated proteins, MAPK1 was predicted to be activated and STAT1/2 inhibited ( Figure 1 ). MAPK1 dysregulation induces chorio-retinal atrophy and optic nerve abnormalities in ZIKV infections and STAT1/2 is involved in antiviral responses; in addition, ZIKV NS5 protein-mediated STAT2 degradation modulates type I and III interferon responses [ 51 , 67 , 68 , 69 ]. Other molecules dysregulated by ZIKV among the top ZIKV dysregulated functions at 48 hpi included over-expressed proteins such as STAT1, IFIT2/3 and HLA-A and under-expressed proteins such as LAMP2 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS studies in human fetal neural progenitor cells and on astrocytic cells, respectively, identified dysregulations in cell proliferation, differentiation and migration and neural cell adhesion molecule (NCAM1) as a receptor for ZIKV infection [ 26 , 49 , 50 ]. iPSC-derived astrocytic cells were also studied and linked ZIKV infection to DNA breakage and reactive oxygen species imbalance in the cells [ 51 , 52 ]. RNA approaches to understanding ZIKV infection have also yielded promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that rapid type I IFN response protected astrocytes from virus-induced cytopathic effects upon infection with flavivirus, tick-borne encephalitis virus (TBEV), JEV, WNV, and Zika virus (ZIKV), thus limiting the spread of these viruses ( 119 ). In addition, type I and type III IFN-independent antiviral pathways were found to be involved in the control of astrocytes during ZIKV infection ( 120 ). In summary, the intrinsic structural antiviral response of astrocytes combined with rapid induction of type I IFNs is instrumental in protecting astrocytes and inhibiting viral replication in the CNS ( 121 ).…”
Section: Antiviral Response In the Cns: Cells Isgs And Mechanismsmentioning
confidence: 99%